Homecoming—Dignity Through Movement at the End of Life: A Qualitative Interview Study With Healthcare Professionals. (January 2022) - Cameron, Fiona; Janze, Anna; Klarare, Anna
Aim: To describe healthcare professionals' and volunteers' experiences of a pathway for movement on a hospice ward. Method: This was a qualitative study with an inductive approach. Data were collected in a hospice setting through 4 focus group interviews with healthcare professionals and volunteers (n = 12). The focus group participants varied in age, profession, and length of experience in palliative care. The interviews were audio recorded, transcribed and analyzed with qualitative content analysis. Results: Dignity through movement at the end of life was the main theme, complemented by 4 sub-themes. Two descriptive sub-themes: "A practical tool to facilitate physical activity" and "Companionship and goals give meaning to the day, " and 2 interpretative sub-themes: "Regaining control and having a choice" and "Feeling normal and alive" based on participants' views of patient experiences. Significance of Results: Indications are that the pathway for movement addresses a wide range of experiences related to different aspects of being human in a difficult situation. Experiences of movement and physical activity can promote wellbeing, dignity, and a sense of feeling "at home" for patients within hospice care. The pathway for movement is simple to set up, offers access to appropriate physical activity and seems to benefit patients both in the early and later phases of palliative care.